2020
DOI: 10.1002/mabi.201900382
|View full text |Cite
|
Sign up to set email alerts
|

Methylcobalamin‐Loaded PLCL Conduits Facilitate the Peripheral Nerve Regeneration

Abstract: The feasible fabrication of nerve guidance conduits (NGCs) with good biological performance is important for translation in clinics. In this study, poly(d,l‐lactide‐co‐caprolactone) (PLCL) films loaded with various amounts (wt; 5%, 15%, 25%) of methylcobalamin (MeCbl) are prepared, and are further rolled and sutured to obtain MeCbl‐loaded NGCs. The MeCbl can be released in a sustainable manner up to 21 days. The proliferation and elongation of Schwann cells, and the proliferation of Neuro2a cells are enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Inspired by the highly aligned microstructure of native nerve fibers, organized topographical guidance and bioactive molecules have been introduced to the inner wall of various types of NGCs to enhance their nerve regeneration ( Huang et al, 2020 ). Linear micropatterns can induce the elongation of SC and nerite orientation of dorsal root ganglion ( Zhang et al, 2020a ). Therefore, in this study the linear micropatterns were created firstly on the PLCL film by using a stamp made from PDMS, which has very low surface energy for anti-adhesion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Inspired by the highly aligned microstructure of native nerve fibers, organized topographical guidance and bioactive molecules have been introduced to the inner wall of various types of NGCs to enhance their nerve regeneration ( Huang et al, 2020 ). Linear micropatterns can induce the elongation of SC and nerite orientation of dorsal root ganglion ( Zhang et al, 2020a ). Therefore, in this study the linear micropatterns were created firstly on the PLCL film by using a stamp made from PDMS, which has very low surface energy for anti-adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, Zhang et al (2018b) found that SCs cultured on 20/40 μm polyester migrate along the stripes, with a higher ratio of L/W compared to those on the flat film. Furthermore, the migration rate of SCs was also increased significantly when being cultured on the 3/3-μm parallel stripe PLCL, which may promote the M2 polarization of macrophage ( Zhang et al, 2020a ). In this study, the microstructures of parallel grooves and ridges were created on the surface of the PLCL film, which could similarly guide the direction of SCs and enhance the ability of migration even though the macroprous structure was further implemented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methylcobalamin and electrical stimulation are commonly used methods in clinic and basic research area, which plays an important role in the treatment of nerve injury and degeneration. Zhang demonstrate that methylcobalamin has the ability to facilitate the recovery of motor and sensory function, and to promote myelination in peripheral nerve regeneration [ 16 ]. Willand think the imminent clinical applicability of acute brief low-frequency electrical stimulation effectively promote axonal regeneration and maximize functional recovery in diverse types of peripheral nerve injuries [ 17 ].…”
Section: Discussionmentioning
confidence: 99%